(untitled) (Journal of Atomic and Molecular Sciences, 2010)
The electronic structure of rutile TiO_2 doped with double nitrogen atoms is studied by the plane-wave ultrasoft pseudopotential method based on the first-principles density functional theory. It has been used to analyze the effect of three doping positions of double N on the relevant band structure. The calculation demonstrates that there exist additional states in the band gap when doping of the rutile TiO_2 with N atoms, and the gap become narrowing. The results imply that the doped two N atoms in the adjacent position form a more intermediate stable level, and the total energy is the minimum.